2021
DOI: 10.1177/23814683211045648
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Willingness to Share Limited Endoscopic Resources: A Brief Report on the Results of a Large Regional Survey

Abstract: Background. In some health care systems, patients face long wait times for screening colonoscopy. We sought to assess whether patients at low risk for colorectal cancer (CRC) would be willing to delay their own colonoscopy so higher-risk peers could undergo colonoscopy sooner. Methods. We surveyed 1054 Veterans regarding their attitudes toward repeat colonoscopy and risk-based prioritization. We used multivariable regression to identify patient factors associated with willingness to delay screening for a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This is consistent with prior work indicating that during times of limited resources, most individuals are willing to delay colonoscopy for a peer at high risk. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with prior work indicating that during times of limited resources, most individuals are willing to delay colonoscopy for a peer at high risk. 24 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior work indicating that during times of limited resources, most individuals are willing to delay colonoscopy for a peer at high risk. 24 About 60% of our sample completed screening within 12 mo of the hospital's reopening of routine endoscopy services. We did find that intentions toward following through with a colonoscopy in the next month did map onto actual screening completion, and we found that as interest in delaying screening increased, patients were less likely to complete a colonoscopy.…”
Section: Discussionmentioning
confidence: 99%